Financial difficulty of Banking management during COVID 19 in Bangladesh - Bari, Md. Saiful (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
Findings point out that the savings rating operations and performances of private business Banks have outperformed these of state-owned industrial banks. The mortgage disbursement techniques of state-owned industrial banks have been now no longer efficient ample to reap required recuperation target. Furthermore, it has additionally been found that the state-owned business banks are increased in all likelihood to be affected via using each and every of the contributory factors a long way larger adversely than non-public business banks. Effective use of company governance, maintaining transparency and accountability in all respect, environment friendly financial savings risk management, bettering managerial efficiency, profitable privatization, lessening political interference and adapting contemporary technological changes, would possibly also enhance the well-known personal loan trouble scenario of state-owned industrial banking region of Bangladesh. Countries throughout the worldwide are going through a risk of an outright disintegration as international supply chain is almost dismantled. Labor mobility too is impeded as human beings are locked down at their homes. Business enterprises, small and large, are each shutdown or closed for an indefinite period. Uncertainties are mounting as households and businesses are dealing with liquidity crisis. The key elements that have been enduring the credit score hassle (i.e. non-performing loans) had been reviewed rigorously. Contributory factors such as: corporate governance, savings management, financial savings regulations, and the degree of political interference had been identified. The first-rate direction of action is that Bangladesh Bank orchestrates a good-sized economic growth focused on repo price of four percentages and lending charge in the range of 5-8 percent.